PENINGKATAN KEMAMPUAN NUMERASI PADA OPERASI PENGURANGAN MELALUI METODE BERMAIN PERAN SISWA KELAS I MI MA’ARIF KEDIWUNG - Nur Khofifah, Luluk; Suratiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve first-grade students’ numeracy skills in subtraction operations at MI Ma’arif Kediwung through the implementation of the role-playing method. The research employed a Classroom Action Research (CAR) design using a cyclical model consisting of planning, action, observation, and reflection stages. The participants were 10 first-grade students, comprising five boys and five girls. Data were collected through tests, observations, and documentation. Quantitative data were analyzed by calculating mean scores, learning mastery percentages, and N-Gain, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings indicated a consistent improvement with a moderate gain category. The class mean score increased from 62 in the pre-cycle to 73 in Cycle I and 85 in Cycle II, while the percentage of students achieving mastery improved from 30% to 90%. The buying-and-selling role-play simulation using coin media helped students understand subtraction concepts in a concrete and contextual manner. Therefore, the role-playing method proved effective in enhancing early-grade students’ numeracy skills and may serve as an alternative instructional strategy for mathematics learning in Islamic elementary schools.